Reconciling observed and modeled temperature and precipitation trends over Europe by adjusting for circulation variability. Issue 15 (8th August 2016) - Saffioti, Claudio; Fischer, Erich M.; Scherrer, Simon C.; Knutti, Reto
Abstract: Europe experienced a pronounced winter cooling of about −0.37°C/decade in the period 1989–2012, in contrast to the strong warming simulated by the Coupled Model Intercomparison Project Phase 5 multimodel average during the same period. Even more pronounced discrepancies between observed and simulated short‐term trends are found at the local scale, e.g., a strong winter cooling over Switzerland and a pronounced reduction in precipitation along the coast of Norway. We show that monthly sea level pressure variability accounts for much of the short‐term variations of temperature over most of the domain and of precipitation in certain regions. Removing the effect of atmospheric circulation through a regression approach reconciles the observed temperature trends over Europe and Switzerland and the precipitation trend along the coast of Norway with the corresponding multimodel mean trends. Key Points: Recent European winter cooling was mostly caused by atmospheric circulation Circulation is a key driver of short‐term climate trends over Europe Accounting for circulation reconciles most observed and simulated trends